Contextualizing Caves within an Animate Maya Landscape: Caves as Living Agents in the Past and Present - Brent K. S. Woodfill (Religions, 2021)
After groundbreaking work by multiple archaeologists in the latter half of the 20th century, caves in the Maya world are currently acknowledged as fundamentally ritual rather than domestic spaces. However, a more nuanced read of the anthropological literature and conversations with Indigenous collaborators in the past and present pushes us to move still farther and see caves not as passive contexts to contain ceremonies directed elsewhere but animate beings with unique identities and personalities in their own right. This article combines archaeological, ethnohistoric, and ethnographic documentation of Maya cave use in central Guatemala to build a foundation for examining caves as living beings, with particular attention played to the role they play as active agents in local politics and quotidian life. Through ritual offerings, neighboring residents and travelers maintain tight reciprocal relationships with specific caves and other geographic idiosyncrasies dotting the landscape to ensure the success of multiple important activities and the continued well-being of families and communities.